Sistem Pendukung Keputusan Teknisi Terbaik PT.Telkom Indonesia Tanjungpinang Menggunakan Metode TOPSIS - Muhammad Faizal; Mochammad Rizki Romdoni; Gunawan Pratama (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2018)
Information is needed in the decision making process. Good and right decisions need to be supported by the availability of accurate, fast and relevant information. With such information, the head of an office or head of an institution or organization can get a complex and specific picture of a decision to be formulated. The decision will be efficient in terms of time because the data can be accessed instantly. In addition, the accuracy of the data is more guaranteed, so that decisions that are formulated will be more precise and can be formulated in a relatively short time. So far, PT Telkom Indonesia Tanjungpinang in making the decision to choose the best technician is not based on qualitative data comparing each existing criterion, so that the assessment is only carried out by the head of the office or asman by selecting the technician who he thinks is the best without considering the required criteria. So the assessment is only based on the results of voting votes and also the calculations carried out are also not computerized, so that old data is often lost from the books. With the Web-Based Best Technician Decision Support System to help the Head of the Office in dealing with the above problems, this system was created using the TOPSIS (Technique For Others Reference by Similarity to Ideal Solution) method with the PHP and Mysql programming languages ​​as the database, as well as the software modeling method using UML.